An Econometric & Systematic Analysis of Thailand's Economic Output, Exports and Imports; Utilizing Vector Error Correction Methodology - Hamza, Ali; Nechchad, Ferdaous (Journal of Business Technology and Economics, 2024)
Thailand, after Indonesia is Southeast Asia's second-largest economy. Exports made up 65.78% of Thailand's GDP in 2022. The present study, using VECM, measures the long-run effect of import & export on the economic growth of Thailand. For this aim, time series data is obtained for the period of 63 years (1960-2022) from WDI website. Based on literature review, we used logarithmic transformation of variables. The data is analyzed in two sections, descriptive statistics including basic measurement, graphics & correlation while inferential statistics includes unit root testing (ADF & PP), Johansen’s Cointegration test, VECM, Impulse response and model error diagnostics. Interestingly Import & Export are found equally contributing to GDP with equal average. The correlation matrix explains significant relation among all variables at α=1%. Stationary of whole series is recorded at 1st difference, I(1). Cointegration test confirms the presence of one co-integrated equation. The VECM incorporates the co-integration model representing negative and statistically C(1) as coefficient of error correction, suggesting the presence of a long-term causal relationship among imports, exports and GDP. Impulse response of LN_GDP & LN_EXP indicates upward impact in them while LN_IMP depict downward trends. The residuals obtained from the Vector Error Correction Model exhibit independent variables (without autocorrelation), follow a normal distribution, and are devoid of heteroskedasticity.